Zinc Finger-Homeodomain Transcriptional Factors (ZHDs) in Upland Cotton (Gossypium hirsutum): Genome-Wide Identification and Expression Analysis in Fiber Development - Abdullah, Muhammad; Cheng, Xi; Cao, Yunpeng; Su, Xueqiang; Manzoor, Muhammad Aamir; Gao, Junshan; Cai, Yongping; Lin, Yi (Frontiers in Genetics, 2018)
Zinc finger homeodomain (ZHD) genes encode a family of plant-specific transcription factors that not only participate in the regulation of plant growth and development but also play an important role in the response to abiotic stress. ZHD family genes have been studied in several model plants, including Solanum lycopersicum, Zea mays, Oryza sativa and Arabidopsis thaliana. However, a comprehensive study of ZHD family genes and their roles in fiber development and pigmentation in upland cotton has not been completed. To address this problem, we selected a brown fiber cultivar for our study; brown color in cotton is one of the most desired colors in the textile industry. Because it has natural coloured fibers, there is less processing and little dying required, which may eliminate dye costs and chemical residues. Using bioinformatics approaches, we identified 37 GhZHD genes from Gossypium hirsutum and then divided these genes into seven groups based on their phylogeny. The GhZHD genes were mostly conserved in each subfamily with minor variations in motif distribution and gene structure. The GhZHD genes were largely distributed on 19 of the 26 upland cotton chromosomes. Among Gossypium genomes, paralogues and orthologues of GhZHD genes were identified and further characterized. Furthermore, among the paralogues, we observed that ZHD family duplications in Gossypium genomes (G. hirsutum, G. arboreum, and G. raimondii) probably derived from segmental duplication or genome-wide duplication (GWD) events. Through a combination of qRT-PCR and proanthocyanidins (PA) accumulation analyses in brown cotton fibers, we concluded that candidate genes involved in early fiber development and fiber pigment synthesis include the following: GhZHD29, GhZHD35, GhZHD30, GhZHD31, GhZHD11, GhZHD27, GhZHD18, GhZHD15, GhZHD16, GhZHD22, GhZHD6, GhZHD33, GhZHD13, GhZHD5 and GhZHD23. This study delivers insights into the evolution of GhZHD genes in brown cotton, provides a valuable resource for further studies, and identifies conditions for improving the quality of brown cotton fiber.